Development Of Lower Limb Stroke Rehabilitation Machine - Amrik Singh, Dalbir Singh Banwait (Universiti Sains Malaysia, 2018)
The function of the lower limb can be affected by stroke, accident or even aging. Paralysis on one side of the body is a common effect of stroke which diminishes the strength and control of the lower limb. The lower limb can be rehabilitated by means of exercise. The passive exercise is when the muscle is moved by the means of external force and the active exercise is when the muscle exerted the force necessary to create the motion. Passive range of motion exercises are for stroke survivors who are left with mild to severe paralysation, or paresis. These exercises can help prevent muscle stiffness and spasticity which is the limited coordination and muscle movement. Resistive exercises involve conscious control of the muscle and physical effort exerted into muscular activity to improve neural path formation. The aim of this project is to develop a combination of rehabilitation system based on Continuous Passive Motion (CPM) and Active Resistive Motion (ARM) which cover the flexion-extension of the hip and knee. The system is providing goal-oriented visual feedback in real-time. The mean value of engagement metric of healthy subjects using this machine with visual feedback was 24.53% higher than without visual feedback. This proved that the use of visual feedback can help the patients to be fully engaged during the rehab session strengthening the neuromotor pathways. The assistive mode of motion is set at three cycles per 120 seconds which allows a high intensity and repetitive form of knee extension and flexion. A desktop computer is used as the data entry and also for data display for monitoring and recording purposes. A simulated paretic limb for a 55 kg subject has carried out the passive mode of motion and an average force of 35 N is obtained. The range of motion of the lower limbs achieved 49.8% of average hip flexion of 120° and 84.8% of average knee flexion of 143.7°. Then healthy leg force measurement is carried out at which the person has exerted the maximum pushing force when the cylinder is at rest in retraction mode and obtained a simulated maximum force of 65 N. Resistive rehabilitation exercise is for patient who has slowly regain some strength. It aims to regain lost movement after stroke by strengthening the neural pathways in the brain that enable the performance of the movement. The patient is required to exert force on the leg and the force being exerted by the patient during the hip-knee joint extension will be measured by the load cell at the foot rest. The reading from the load cell is taken as an input to a control system within myRIO to determine whether enough force has been applied to allow the motion. A pre-set force value of 10 N is set in ARM.The system will only complete the hip-knee flexion-extension motion if the paretic limb has achieved the threshold force value and it will end the process when it is unable to achieve the threshold value. This provides a mean for quantitatively monitoring the motor recovery during rehabilitation. This active mode of motion provides positive feedback on the recovery of the muscle strength that motivates the patient to work harder to overcome the threshold force value. The developed system highlight the advantages of goal-oriented feedback on the level of engagement during rehabilitation, the system in driving the actuators, providing suitable resistance level for active exercise based on closed loop control system and to record the achievement of the patient.